Somatotype of Male Rugby Sevens Players from the Juan de Castellanos University Foundation (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2022)
Introduction: Rugby is a team sport in which the physical and physiological characteristics of athletes must be considered according to their playing positions. Forwards experience more physical collisions than backs and, therefore, should have higher muscle mass and a somatotype in which mesomorphy and endomorphy prevail over ectomorphy—that is, they should have robustness, large joints, and predominant muscle mass.Objective: This research aimed to identify the somatotype of male athletes from the Rugby Sevens team at the Juan de Castellanos University Foundation.Methodology: This is a descriptive, non-experimental, cross-sectional study with a quantitative approach. Fourteen athletes were evaluated, with an average age of 22.22 ± 1.67 years, an average weight of 71.36 ± 10.12 kg, and an average height of 1.72 ± 0.04 m.Results: The results show the prevalence of a mesomorphic-ectomorphic somatotype in both backs and forwards, characterized by linear body shape and low muscle volume relative to height.Conclusion: For improved performance, it is necessary to aim for a meso-endomorphic somatotype through proper nutrition and a training plan focused on muscle hypertrophy, addressing the morphofunctional demands of rugby.